Integrated rice–fish farming gives farmers in Laos’ Sanamxay region a new lease on life - Samaddar, Ayan (2024)
Laos’ economy is one of the fastest-growing in Southeast Asia, with a lower-middle income, a markedly rising urbanization and population density and falling rates of malnutrition (GHI 2019; World Bank 2022). Although agriculture is the main source of income, livelihood and nutritional security in Laos, rice has historically been the country’s most significant staple food grain grown (CIA 2023), and there have been significant increases in rice crop area and productivity (World Bank 2022). The southern province of Attapeu is the focus of this report. However, the overall image of rice–fish production systems in the region is unknown because of the paucity of statistical data and pertinent literature, which makes it difficult for rice–fish production systems to contribute more in the future to a wide range of sustainable development goals. Therefore, attention has been given to grasp the potential and impact of three prototype experimental rice–fish farming systems in Attapeu’s Sanamxay District. It has led to the prediction of a possible agroecological transition route through integrated rice–fish farming in the region.